2005
DOI: 10.1007/s11892-005-0024-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress: Changes in pregnancy and with gestational diabetes mellitus

Abstract: Pregnancy is susceptible to oxidative stress and antioxidant defenses can be altered in response to elevated levels of oxidative stress. Limited data in gestational diabetes mellitus (GDM) suggest that products of lipid peroxidation may be increased and antioxidant enzyme activities decreased, although the results have been inconsistent. As in type 2 diabetes mellitus (T2DM), glycemic levels in patients with GDM correlate with concentrations of lipid peroxides. The effects of supplementation with antioxidants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 52 publications
(110 reference statements)
0
71
1
2
Order By: Relevance
“…Other studies have shown that oxidative stress is increased during pregnancy (6,11,22). When this increase is not associated with an optimal antioxidant status, harmful effects could arise that include hypertension, diabetes, preeclampsia, intrauterine growth retardation, abortion and teratogenic processes (7,23).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that oxidative stress is increased during pregnancy (6,11,22). When this increase is not associated with an optimal antioxidant status, harmful effects could arise that include hypertension, diabetes, preeclampsia, intrauterine growth retardation, abortion and teratogenic processes (7,23).…”
Section: Discussionmentioning
confidence: 99%
“…The high metabolic rate of the placenta leads to increased generation of free radicals, biomarkers of which were observed in maternal circulation (6). The concentration of lipoperoxides in cord blood is only 30% of that in maternal blood, suggesting that the placenta suppresses lipoperoxide formation or transplacental passage, protecting the fetus from the action of these free radicals (7).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, free-radical-catalysed peroxidation of arachidonic acid independent of cyclooxygenase results in formation of PGF2-like compounds, namely F2-isoprostanes. Among them, 8-iso-prostaglandin F2a (8-iso-PGF2a) is an important marker of endogenous lipid peroxidation [41]. The functional consequence of lipid peroxidation is an increase in membrane fluidity and permeability [38].…”
Section: Indicators Of Oxidative Stress In Gdmmentioning
confidence: 99%